Lateralized Eye Use Towards Video Stimuli in Bearded Dragons (Pogona vitticeps) - Frohnwieser, A.; Pike, T.W.; Murray, J.C.; Wilkinson, A. (Animal Behavior and Cognition, 2025)
Lateralized eye use is thought to increase brain efficiency, as the two hemispheres process different information perceived by the eyes. It has been observed in a wide variety of vertebrate species and, in general, information about conspecifics appear to elicit a left eye preference whilst information about prey elicits the opposite. In reptiles, this phenomenon has only been investigated using live conspecifics in agonistic contexts, and so it is not clear whether it can be found when using video stimuli. Here, bearded dragons (Pogona vitticeps) were presented with videos of female conspecifics and prey that either moved or were stationary, along with a control video of an empty background. Females exhibited a left eye bias towards conspecifics but males did not, however, both sexes looked at conspecifics significantly longer than prey. Further, animals used their left eye significantly longer when viewing moving stimuli of both categories. These results suggest that, in lizards, lateralized eye use when viewing conspecifics may be controlled by sex, and strongly influenced by stimulus movement. This study therefore provides important insights into the role of lateralized processing in lizard perception, and sets the scene for future work investigating the role of sex on perception of conspecifics and the role of motion in lateralized eye use.
Keywords: Lateralized eye use; Perception; Bearded dragon; Video stimuli